The Implementation of CLIL at Primary School : Teacher’s Perspectives and Challenges - Nur Siwi Suci Anggraini; Ahmad Munir; Oikurema Purwati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Indonesia has adopted CLIL especially for bilingual schools and those using an International curriculum. Many studies describe the advantages of CLIL. However, it turns out that only a few have presented research on how the teacher's perspective on CLIL is and what the challenges are. This study aims to explore the teacher's perspective on CLIL implementation and the challenges of its implementation. This qualitative study aims to investigate and explore primary school teacher’s perspectives and challenges of CLIL implementation in primary school. She is actually science teacher but have pretty good skill in English. Data was obtained from a teacher through open-ended question and semi-structure interview about her persprctives and challenges during implementation of CLIL. The result of this study are clearly demonstrated that teacher’s perpectives were aimed toward CLIL characteristics, CLIL implementation, and students' knowledge of the topic and language. Furthermore, the challenges arise were mostly on the side of both teachers and pupils. This study reinforces previous study about teacher perspective of implementation CLIL but in this stidy explore what are the challenges too because CLIL uses target language such or foreign language so it will be arise challenges during implementation. Therefore, this article will be an afterthought for schools that will use CLIL